2020
DOI: 10.18868/cte.02.060120.14
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, Barriers, Motivation, and Adaption of Blended Learning

Abstract: Educational Institutions worldwide are transitioning to blended learning where technology is used and supplement traditional face-to-face instruction. This study investigated the knowledge, attitude, barrier, motivation, and adaption of blended learning in one of the uprising HEI in Mindanao, Saint Michael College of Caraga. The study was conducted to 150 faculty, both full-time and part-time in basic education and tertiary level. A descriptive correlational and causal design utilized the data in describing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
(12 reference statements)
1
1
0
Order By: Relevance
“…A favorable evaluation of gamification in education turned out to be the strongest predictor of intention to use gamification. Furthermore, we partly confirmed our predicted model as attitude mediated the relationship between tested familiarity with gamification, past use, and openness to experience and intention of future use, which matches findings of similar research on ICT adoption [17]- [19], [30]- [32], [42], [43]. Self-assessed knowledge of gamification did not predict future intention to use it in any way, and openness contributed only through a positive attitude, while other personality traits did not play a significant role.…”
Section: Open-ended Responsessupporting
confidence: 88%
See 1 more Smart Citation
“…A favorable evaluation of gamification in education turned out to be the strongest predictor of intention to use gamification. Furthermore, we partly confirmed our predicted model as attitude mediated the relationship between tested familiarity with gamification, past use, and openness to experience and intention of future use, which matches findings of similar research on ICT adoption [17]- [19], [30]- [32], [42], [43]. Self-assessed knowledge of gamification did not predict future intention to use it in any way, and openness contributed only through a positive attitude, while other personality traits did not play a significant role.…”
Section: Open-ended Responsessupporting
confidence: 88%
“…For instance, multiple studies showed attitudes toward technology significantly predict teachers' intention to use said technology and also help explain the relationship between behavioral intentions and other constructs [3]. Knowledge or awareness is one such variable as it is an important predictor of behavior, either directly as familiarity with an object such as ICT tools makes it more likely to use it as part of instruction [17], or indirectly through forming more positive attitudes [18], [19].…”
Section: Attitude Familiarity Experience and Personality In Relation ...mentioning
confidence: 99%